Correlation Between White Matter Injury Identified by Neonatal Diffusion Tensor Imaging and Neurodevelopmental Outcomes Following Term Neonatal Asphyxia and Therapeutic Hypothermia: An Exploratory Pilot Study. (September 2019) - Gerner, Gwendolyn J.; Newman, Eric I.; Burton, V. Joanna; Roman, Brenton; Cristofalo, Elizabeth A.; Leppert, Mary; Johnston, Michael V.; Northington, Frances J.; Huisman, Thierry A.G.M.; Poretti, Andrea
Aim: Hypoxic-ischemic encephalopathy is associated with damage to deep gray matter; however, white matter involvement has become recognized. This study explored differences between patients and clinical controls on diffusion tensor imaging, and relationships between diffusion tensor imaging and neurodevelopmental outcomes. Method: Diffusion tensor imaging was obtained for 31 neonates after hypoxic-ischemic encephalopathy treated with therapeutic hypothermia and 10 clinical controls. A subgroup of patients with hypoxic-ischemic encephalopathy (n = 14) had neurodevelopmental outcomes correlated with diffusion tensor imaging scalars. Results: Group differences in diffusion tensor imaging scalars were observed in the putamen, anterior and posterior centrum semiovale, and the splenium of the corpus callosum. Differences in these regions of interest were correlated with neurodevelopmental outcomes between ages 20 and 32 months. Conclusion: Therapeutic hypothermia may not be a complete intervention for hypoxic-ischemic encephalopathy, as neonatal white matter changes may continue to be evident, but further research is warranted. Patterns of white matter change on neonatal diffusion tensor imaging correlated with neurodevelopmental outcomes in this exploratory pilot study.